2021
DOI: 10.1108/scm-09-2020-0470
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain agility responding to unprecedented changes: empirical evidence from the UK food supply chain during COVID-19 crisis

Abstract: Purpose The COVID-19 outbreak has imposed extensive shocks embracing all stages of the food supply chain (FSC). Although the magnitude is still unfolding, the FSC responds with remarkable speed, to mitigate the disruptive consequences and sustain operations. This paper aims to investigate how operationalising supply chain agility (SCA) practices has occurred amid the COVID-19 crisis and expectations for how those practices could transform the supply chain in the post-COVID-19 era. Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 103 publications
(116 reference statements)
2
66
0
4
Order By: Relevance
“…Third, the upheavals resulting from a pandemic are sudden and can take the form of opportunities and threats that are specific to each case setting. This is supported by academic literature; how Covid-19 has created new opportunities in certain industries (Do et al, 2021).…”
Section: Theoretical Contributionsmentioning
confidence: 70%
See 1 more Smart Citation
“…Third, the upheavals resulting from a pandemic are sudden and can take the form of opportunities and threats that are specific to each case setting. This is supported by academic literature; how Covid-19 has created new opportunities in certain industries (Do et al, 2021).…”
Section: Theoretical Contributionsmentioning
confidence: 70%
“…The ongoing Covid-19 pandemic has created a new era worldwide and up to date many businesses still continue to understand the crippling effects it has on various aspects of their daily operations (Do et al, 2021). This virus revealed that events characterized by unprecedented uncertainty impinged on normal demand and supply patterns, causing a significant economic crisis, sales declines and disruptions in the supply chain (SC) system (Parast and Subramanian, 2021;Kumar and Abdin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…1 . However, unlike recurring operational disruptions, a crisis triggers extreme demand- and supply-shocks such as panic buying and changes in purchasing behaviour (Burgos and Ivanov 2021 ; Do et al 2021 ) along with severe shortages of essential resources and labour (Dubey et al 2021 ; Ozdemir et al 2022 ; Raj et al 2022a ).…”
Section: Supply Chain Management In Times Of Crisis: Terminological F...mentioning
confidence: 99%
“…In this context, SCM literature contains accounts on the evaluation of orchestration strategies for supply stability and for innovative and value-added services that harness the specialisation and expertise of supply chain actors (Bian et al 2021 ; Sumukadas 2021 ). There are also expositions on the importance of agility and flexibility for addressing volatility issues of demand based on SCM lessons learnt from dealing with previous crises (Do et al 2021 ; Harland 2021 ). However, the dominant theoretical and practical challenge remains to understand SCM complexities in times of crisis for improving supply chain resilience, with debates concerning a range of management issues such as the prioritisation of localisation (or regionalisation) over globalisation and inshoring over offshoring (Dewick et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear why rates were elevated in grain milling/storage sites after adjusting for various local and workplace risk factors, but it might be related to the response to the surge in demand for flour, particularly early in the pandemic ( Do et al , 2021 ). Workplace level COVID-19 risks appear to be associated with neighbourhood deprivation, but this is sensitive to the radius chosen: COVID-19 rates decreased with lower average deprivation in a 5 km radius, but this was not apparent with a 1 km radius.…”
Section: Discussionmentioning
confidence: 99%